2008
DOI: 10.2136/vzj2007.0079
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Soil Micromorphological Features on Water Flow and Herbicide Transport in Soils

Abstract: A: WF, weighting factor. S S : V Z M The impact of varying soil micromorphology on soil hydraulic proper es and, consequently, on water fl ow and herbicide transport observed in the fi eld is demonstrated on three soil types. The micromorphological image of a humic horizon of Haplic Luvisol showed higher-order aggregates. The majority of detectable pores corresponding to the pressure head interval between −2 and −70 cm were highly connected, separa ng higher-order peds with small intrapores that possibly forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 34 publications
5
51
0
1
Order By: Relevance
“…Aggregate coatings and biopore walls are characteristic soil structural features (e.g., Gerke and Köhne, 2002;Kodešová, 2009;Kodešová et al, 2011Kodešová et al, , 2015Rogasik et al, 2014) that are of great importance when attempting to describe preferential flow and transport processes in soils (e.g., Gerke, 2012;Kodešová, 2009;Kodešová et al, 2008Kodešová et al, , 2009Kodešová et al, , 2010Kodešová et al, , 2012. Clay-organic coatings often cover aggregates and biopores in the clay-illuviation Bt-horizons of Luvisols (IUSS Working Group WRB, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregate coatings and biopore walls are characteristic soil structural features (e.g., Gerke and Köhne, 2002;Kodešová, 2009;Kodešová et al, 2011Kodešová et al, , 2015Rogasik et al, 2014) that are of great importance when attempting to describe preferential flow and transport processes in soils (e.g., Gerke, 2012;Kodešová, 2009;Kodešová et al, 2008Kodešová et al, , 2009Kodešová et al, , 2010Kodešová et al, , 2012. Clay-organic coatings often cover aggregates and biopores in the clay-illuviation Bt-horizons of Luvisols (IUSS Working Group WRB, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Kodešová et al (2012), are shown in Table 1. Kodešová (2009) ;Kodešová et al (2008Kodešová et al ( , 2009) reported intensively developed blocky, and large and long prismatic aggregates in the Bt1 and Bt2 horizons, respectively. Soil aggregates in the Bt1 and Bt2 horizons were covered by clay and organic matter coatings.…”
Section: Introductionmentioning
confidence: 99%
“…The micromorphological analysis was also used to explain various soil water retention without the extending flow modeling by Constantini et al (2006), Juhász et al (2007) and Pires et al (2008). Kodešová et al (2008) investigated the impact of varying soil micromorphology on soil hydraulic properties and consequently on water flow and herbicide (chlorotoluron) transport observed in the field on three soil types (Haplic Luvisol, Greyic Phaeozem, Haplic Cambisol). The field experimental method was described in detail by Kočárek et al (2005).…”
Section: Soil Micromorphology Methods For Multiple Domain Parameter Ementioning
confidence: 99%
“…However, Jarvis (2007) and Köhne et al (2009a) argued that macropores (pores causing the physical non-equilibrium of water flow close to saturation) are pores with an equivalent diameter larger than about 300-500 µm (corresponding to a pressure head of -10 and -6 cm), Kodešová at al. (2006Kodešová at al. ( , 2008Kodešová at al.…”
Section: Benefits and Limitations Of Soil Micromorphology Approach Fomentioning
confidence: 99%
See 1 more Smart Citation